(untitled) (Clinics, 2013)
OBJECTIVE: The ideal ratio between liver graft mass and recipient body weight for liver transplantation in small infants is unknown; however, if this ratio is over 4%, a condition called large-for-size may occur. Experimental models of large-for-size liver transplants have not been described in the literature. In addition, orthotopic liver transplantation is marked by high morbidity and mortality rates in animals due to the clamping of the venous splanchnic system. Therefore, the objective of this study was to create a porcine model of large-for-size liver transplantation with clamping of the supraceliac aorta during the anhepatic phase as an alternative to venovenous bypass. METHOD: Fourteen pigs underwent liver transplantation with whole-liver grafts without venovenous bypass and were divided into two experimental groups: the control group, in which the weights of the donors were similar to the weights of the recipients; and the large-for-size group, in which the weights of the donors were nearly 2 times the weights of the recipients. Hemodynamic data, the results of serum biochemical analyses and histological examination of the transplanted livers were collected. RESULTS: The mortality rate in both groups was 16.5% (1/7). The animals in the large-for-size group had increased serum levels of potassium, sodium, aspartate aminotransferase and alanine aminotransferase after graft reperfusion. The histological analyses revealed that there were no significant differences between the groups. CONCLUSION: This transplant method is a feasible experimental model of large-for-size liver transplantation.